Lattice Boltzmann simulations of liquid crystal hydrodynamics - Denniston, C; Orlandini, E; Yeomans, J (2001)
The liquid crystal hydrodynamics were simulated using a lattice Boltzmann algorithm. Both the isotropic and nematic phases were analyzed by the equations of motion written in terms of a tensor order parameter. The non-Newtonian flow properties such as shear thinning and shear banding, the backflow effects and the hydrodynamics of topological defects were included in the simulations.